1974
DOI: 10.1063/1.1663124
|View full text |Cite
|
Sign up to set email alerts
|

New absorptive mode reflective liquid-crystal display device

Abstract: A new reflective dichroic liquidcrystal display device Appl. Phys. Lett. 30, 619 (1977); 10.1063/1.89282 Liquidcrystal thermooptic effects and two new information display devicesA new liquid-crystal alphanumeric display device is described. The device is of the guest-host type and .involves the orientational change of a pleochroic dye (guest) ill a cholesteric liquid-crystal mixure (host) by the application of an external electric field. The cholesteric nature of the host permits the operation of the device in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(81 citation statements)
references
References 7 publications
2
79
0
Order By: Relevance
“…The effect observed, termed the guest-host effect, is 2 thought to be primarily due to the steric interactions between the dye and the LC, i.e. van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect observed, termed the guest-host effect, is 2 thought to be primarily due to the steric interactions between the dye and the LC, i.e. van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the alignment of the dipole moment of the dye with the director of the LC offers the prospect of a coloured liquid crystal display (LCD) that can be switched to a transparent state in an on-off fashion with an external electric field [1][2][3][4]. Additionally, it has been observed that the electro-optic response time of nematic LCs can be improved by dye dopants with large dipole moments, which is also of great interest in display applications [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the short-wavelength bands were calculated to arise from a number of different transitions, in some cases with different values of β, as listed in Table 3. The calculated dichroic ratios of these bands were determined by summing the absorbance contributions from the total number of transitions, m, contributing to each band, according to Equation (5), which is derived from Equations (2) and (3), and where S ϕ i is the calculated order parameter of each transition determined using Equation (4). This approach assumes that the absorption coefficient of each transition, i, is proportional to the calculated oscillator strength, f i , and that all the transitions provide a wavelength-independent contribution to the band.…”
Section: Calculated Dichroic Order Parametersmentioning
confidence: 99%
“…In general, display technology has been the most widely proposed application for these systems because the incorporation of a suitable dye or mixture of dyes within a host in a liquid crystal cell provides a device that may be switched from a transmitting state to an absorbing state. Many variations on this basic concept have been proposed, for example, dual-layer devices [2] or devices incorporating quarter-wave plates [3] that do not require polarisers, phase-change devices that utilise cholesteric host molecules [4] and scattering devices utilising smectic A hosts [5]. Such guest-host systems have also been proposed for other wide-ranging applications, such as smart windows [6], solar cell precursors [7], security devices [8], diffraction gratings [9] and polarisers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since a contact lens is, however, often not thicker than 120 μm, a polarizer free approach is needed as no sufficiently thin polarizers are commercially available at present. Therefore, a transmissive guest-host configuration as proposed by White and Taylor [3] was chosen with a homeotropic alignment and a twist angle of 180°. A conceptual drawing of how such a liquid crystal (LC) based contact lens display may look like is presented in Figure 1.…”
Section: Background and Objectivesmentioning
confidence: 99%